Facile Synthesis of Porous CuO Nanosheets as High-performance NO2 Gas Sensor. Issue 193 (13th October 2018) - Budhiraja, Narender; Sapna,; Kumar, Vinod; Tomar, Monika; Gupta, Vinay; Singh, S. K.
Abstract: Present work reports on the synthesis of 2-dimensional (2D) CuO nanostructures with enhanced NO2 gas sensing properties by a facile solvothermal method. 2D CuO nanostructures were investigated using X-ray diffraction, Field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and Fourier transform infrared (FTIR). FESEM studies revealed as synthesized nanostructures possess a nanosheets like morphology. Gas sensing studies showed that sensor of as prepared 2D CuO nanostructures exhibit enhanced gas sensing properties with excellent selectivity towards NO2 as compared to other volatile gases such as ethanol, methanol and acetone.